A comparative study of mechanical and machining performance of polymer hybrid and carbon fiber epoxy composite materials. Issue 9 (November 2021) - Erturk, A Tamer; Yarar, Eser; Vatansever, Fahri; Sahin, Alp Eren; Kilinçel, Mert; Alpay, Yakup Okan
Fiber-reinforced plastics are known as advanced composite materials thanks to their high strength and lightweight features. Carbon fiber reinforced polymers (CFRPs) are one of the high-performance and high-cost fiber-reinforced polymer (FRPs) materials. They are used in several high-performance engineering applications such as motorsports, marine, aviation, energy and defense industry. The cost of carbon fiber is higher compared to many other materials, more competitive and cost-effective productions will spur the demand for composite parts exponentially. Thus, hybrid laminate composite containing carbon and glass fiber materials were manufactured as an alternative for CFRP materials. Because using glass fiber prepreg instead of carbon fiber prepreg will lead the material to become cheaper. However, machining of the FRP materials is still an important issue. For this reason, the present study is focused on the mechanical and machining performance of the polymer hybrid and carbon fiber epoxy composites.